Clitics in phonology, morphology and syntax - Gerlach, Birgit; Grijzenhout, Janet (Linguistik aktuell, 2000)
This book contains fourteen articles that reflect current ideas on the phonology, morphology, and syntax of clitics. It covers the forms and functions of clitics in various typologically diverse languages and presents data from, e.g. European Portuguese, Macedonian, and Yoruba. It extensively deals with the prosodic structure of clitics, their morphological status, clitic placement, and clitic doubling. The form and behavior of clitics with respect to tonal phenomena and in verse are discussed in two articles (Akinlabi & Liberman, Reindl & Franks). Other articles address the prosodic represent.